Classical and symmetrical horizontal convection: detaching plumes and oscillations. (10th June 2020) - Reiter, Philipp; Shishkina, Olga
Abstract : Abstract : Classical and symmetrical horizontal convection is studied by means of direct numerical simulations for Rayleigh numbers Ra up to 3 × 10 12 and Prandtl numbers Pr=0.1, 1 and 10. For both set-ups, a very good agreement in global quantities with respect to heat and momentum transport is attained. Similar to Shishkina & Wagner ( Phys. Rev. Lett., vol. 116, 2016, 024302), we find Nusselt number Nu versus Ra scaling transitions in a region 10^8Ra10^11 . Above a critical Ra, the flow undergoes either a steady–oscillatory transition (small Pr ) or a transition from steady state to a transient state with detaching plumes (large Pr ). The onset of the oscillations takes place at Ra Pr^-1≈ 5× 10^9 and the onset of detaching plumes at Ra Pr^5/4≈ 9× 10^10 . These onsets coincide with the onsets of scaling transitions.